The twisted dead - Coates, Darcy (Coates, Darcy. Gravekeeper, 2023)
"USA Today bestseller and rising queen of atmospheric horror Darcy Coates returns with a ghost story that will haunt you long after the final page. Keira is ready for a normal life. Hunted and haunted, all she wants is to put her mysterious past behind her and move forward with her new friends as Blighty Graveyard's groundskeeper. But then she receives an invitation to dinner at the local recluse's crumbling ancestral estate. The mansion is steeped in history that is equal parts complicated and bloody--and at its center is the man who once tried to kill her, now begging for her help. Dane Crispin believes his home is haunted--and that the unquiet dead clawing through the ancient house are after him. Unnerved but intrigued, Keira opens her second sight and discovers he's right: resentful specters cling to Dane... and if she can't find a way to stop them, threaten to consume everything in their path. There's something dark happening in the world beyond most peoples' vision, and if Keira isn't able to sever the ties between the living and the dead, the chained spirits may not be the only things twisted beyond saving"--